From the heavens to the streets: Pune’s Wayside Shrines - Larios, Borayin Maitreya (South Asia multidisciplinary academic journal, 2018)
This article presents the results from brief ethnographic research conducted in 2016 in the city of Pune, Maharashtra. Through two case studies of wayside shrines in Pune—the first, a tiny pavement shrine which is steadily growing in popularity, and the second, a small shrine turned into an extravagant temple in just a few years—I consider them as more than just spontaneous expressions of devotion. Taking into consideration the roles that urban conditions and social configurations have been playing in how social actors forge connections between localities and different communities, this paper will look at how these shrines can be spaces of creative subversion of the established socio-religious order and its structures of power. In in this contribution, I argue that the wayside shrine reveals the blurred boundaries between the rural and the urban, the sacred and the mundane, the institutionalized and the popular as well as the legal and the illegal.
Gesehen am 26.11.2018